SECONDARY METABOLITE OF SUMBAWA ALGAE AND ITS POTENTIAL AS NATURAL PRESERVATIVE CANDIDATES (AN ANTIMICROBIAL STUDIES) - Baso Manguntungi; Arlinda Puspita Sari; Ariandi Ariandi; Leggina Rezzy Vanggy; Robby Erlangga; Muhammad Abdi Mahesa (BIOTROPIA, 2022)
Pathogenic bacterial contamination was a serious matter due to its capability in reducing food quality and health. This study aimed to select various types of algae in Luk Coast, Sumbawa Regency that have the potential to produce antibacterial compounds for natural food preservatives. Algae on Luk Coast was identified by means of morphological characters, followed by sample preparation and extraction of secondary metabolites (bioactive compounds). Algae extracts were used in antibacterial tests against food spoilage bacteria, such as Escherecia coli, Staphylococcus aureus, Salmonella thypi, Enterobacter cloacae and Pantoea agglomerans. Five types of algae identified were Padina sp., Halimeda opuntia, Sargassum horneri, Sargassum crassifolium and Galaxaura rugose. The five algae have the growth-inhibiting ability toward the tested bacteria. The highest inhibition zone was obtained from the 100% algae extract concentration.